Enhancing Criminal Sentencing Options in Wisconsin: The State and County Correctional Partnership - Engle, Par Jason; Weimer, David L. (My University, 2005)
The State and County Correctional Partnership proposes providing Wisconsin counties with annual block grants and imposing fees for state prison time served by felons who commit less serious crimes. This policy change would seek to create an environment in which counties can find innovative ways to divert felons safely and cost-effectively from incarceration in state prisons.